Longitudinal Evaluation of Sexual Function in a Cohort of Pre‐ and Postmenopausal Women. (4th May 2015) - Burri, Andrea; Hilpert, Peter; Spector, Timothy
Abstract Introduction Aspects of women's sexual functioning that have received relatively little attention are its stability and how changes in the different sexual response domains influence each other over time. Aim The aim of this study was to describe the changes and to evaluate the stability of self‐reported sexual functioning over a 4‐year period in a population sample of British women. Methods A 4‐year follow‐up study on N = 507 women, including 178 pre‐ and 329 postmenopausal women, was conducted. The validated Female Sexual Function Index (FSFI) was applied. Main Outcome Measure A multigroup path analytical model was used to examine autoregressive effects (the effect of a domain on itself at a later point in time) and cross‐lag effects (one variable affecting another variable at a later point in time) across all FSFI domains of sexual functioning between pre‐ and postmenopausal women. Results Overall, the proportion of postmenopausal women suffering from a sexual dysfunction at measurement point 1 (T1) was higher compared with premenopausal women (pre: 34.3% vs. post: 14.5%). However, both groups showed a comparable number of women developing a sexual problem (pre: 22.2% vs. post: 23.2%) or improving their sexual functioning (7.4% vs. 7.6%) after the 4 years. Furthermore, path model analyses revealed that each domain at T1 significantly predicted its level 4 years later (βs ranging from 0.33 for arousal to 0.57 for lubrication), with the exception of sexual satisfaction. In terms of cross‐lag effects, the changes in all domains except for pain were predicted either by levels of desire, arousal, or orgasm at T1 (βs ranging from 0.18 to 0.36) in both groups. Conclusions Women's sexual functioning was moderately stable across the 4 years. The main predictors of changes in sexual functioning and satisfaction were desire and arousal, highlighting their role as possible key players in women's sexual health. Burri A, Hilpert P, and Spector T. Longitudinal evaluation of sexual function in a cohort of pre‐ and postmenopausal women. J Sex Med 2015;12:1427–1435.